Development of an open source library for reinforced concrete membrane element analysis. (December 2021) - Mello, Andre Felipe Aparecido; Trautwein, Leandro Mouta; Almeida, Luiz Carlos; Souza, Rafael Alves
Abstract: In the 1960's, concrete structures subjected to plane stresses started being idealized as a combination of two-dimensional components called membrane elements. After several research groups having collected experimental data from reinforced concrete panels, material's constitutive models were improved to better describe shear behavior. The Modified Compression Field Theory (MCFT) was developed by University of Toronto's research team and made good predictions for a wide range of structures. Much later, the Disturbed Stress Field Model (DSFM) was born as an upgrade to the previous model, correcting some deficiencies found in specific situations. This paper contributes in this field by developing an open source Microsoft.NET library, named RCMembrane, for analysis of membrane elements by MCFT and DSFM. The results were validated by comparing numerical solution to the experimental data of 72 reinforced concrete panels. For Disturbed Stress Field Model (DSFM), a new relation is proposed for minimizing concrete's compression softening effect in panels subjected to tensile stresses. In general, RCMembrane's solution algorithm obtained very near load capacity prediction for those two distinct formulations, with a slightly smaller coefficient of variation in DSFM results. Next, RCMembrane must be applied to full finite element formulations, so further conclusions can be taken from numerical simulations of usual reinforced concrete structures.